Development and Implementation of a Child Welfare Workforce Strategy to Build a Trauma-Informed System of Support for Foster Care. (May 2016) - Kerns, Suzanne E. U.; Pullmann, Michael D.; Negrete, Andrea; Uomoto, Jacqueline A.; Berliner, Lucy; Shogren, Dae; Silverman, Ellen; Putnam, Barbara
Effective strategies that increase the extent to which child welfare professionals engage in trauma-informed case planning are needed. This study evaluated two approaches to increase trauma symptom identification and use of screening results to inform case planning. The first study evaluated the impact of training on trauma-informed screening tools for 44 child welfare professionals who screen all children upon placement into foster care. The second study evaluated a two-stage approach to training child welfare workers on case planning for children's mental health. Participants included (a) 71 newly hired child welfare professionals who received a 3-hr training and (b) 55 child welfare professionals who participated in a full-day training. Results from the first study indicate that training effectively increased knowledge and skills in administering screening tools, though there was variability in comfort with screening. In the second study, participants self-reported significant gains in their competency in identifying mental health needs (including traumatic stress) and linking children with evidence-based services. These findings provide preliminary evidence for the viability of this approach to increase the extent to which child welfare professionals are trauma informed, aware of symptoms, and able to link children and youth with effective services designed to meet their specific needs.